Karakteristik Penderita Dispepsia di RSUD Prof. DR. Margono Soekarjo Purwokerto - Setyono, Joko; Prastowo, Agus; Saryono, (Jurusan Keperawatan FIKES UNSOED, 2006)
Life style and eat pattern changes are becoming one of the cause the digestive problems. Dyspepsia is one of the most digestive problems in patients. Dyspepsia can be caused by cigarettes, decreased of pressure of the lower sphincter oesophagus, emotionally stress, food which triggering sour secretion of abundant stomach like alcohol and coffee. This research aimed to know patient characteristic of dyspepsia at RSUD. Prof. Dr. Margono Soekarjo Purwokerto. This research is research of descriptive. This research has done in July 2005. Characteristic data of subject research taken by questionnaires. The Result shows that over a half of subject research is woman, of old age more than 40 year, lower education, and unemployed. Small parts of subject research are usually alcohol, coffee, and cigarette consumer. Almost ofall subject have normal nutrition status.